2018 AIAA/ASCE/AHS/ASC Structures, Structural Dynamics, and Materials Conference 2018
DOI: 10.2514/6.2018-0462
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Folding Wing-Tip Devices for Gust Loads Alleviation

Abstract: High aspect ratio wings have been the focus of recent aircraft designs for improved fuel consumption through reducing induced drag. The increase in wing span has also led to folding wing-tips being introduced as a solution for meeting airport gate requirements. Recent studies have suggested such a folding wing-tip solution may be incorporated with spring devices in order to provide an additional gust loads alleviation ability in flight. The current work examines the suitability of using the Doublet-Lattice Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
3
1
0
Order By: Relevance
“…A previous study 3 investigating non-zero-value hinge angle configurations and variation in the folding hinge stiffness demonstrated that the peak wing root bending moment could be reduced by allowing the wing-tip to fold during gust encounters. This finding agrees with several other studies [4][5][6] that also utilized simple passive means for controlling the folding motion. All these studies found that low hinge stiffness in their respective passive system gave a good level of gust load alleviation performance, however further gains could be obtained if the responsiveness of the folding action could be improved.…”
Section: Introductionsupporting
confidence: 93%
“…A previous study 3 investigating non-zero-value hinge angle configurations and variation in the folding hinge stiffness demonstrated that the peak wing root bending moment could be reduced by allowing the wing-tip to fold during gust encounters. This finding agrees with several other studies [4][5][6] that also utilized simple passive means for controlling the folding motion. All these studies found that low hinge stiffness in their respective passive system gave a good level of gust load alleviation performance, however further gains could be obtained if the responsiveness of the folding action could be improved.…”
Section: Introductionsupporting
confidence: 93%
“…A previous study by the authors 2 investigating non-zero-value hinge angle configurations and variation in the folding hinge stiffness demonstrated that the peak wing root bending moment could be reduced by allowing the wingtip to fold during gust encounters. This finding agrees with several other studies [3][4][5] that showed that a lower folding hinge stiffness tended to improve the gust load alleviation performance.…”
Section: Introductionsupporting
confidence: 93%
“…It was found that a low hinge stiffness gave a good level of gust load alleviation performance, with results suggesting further gains could be obtained if the responsiveness of the folding action could be improved. Several other studies [16][17][18] that also utilized simple passive means for controlling the folding motion all concluded with similar findings regarding the requirement of low hinge stiffness as well. More complex solutions have been proposed to address this issue, including the use of nonlinear spring systems [19,20] and bi-stable constructs [21] to provide the required hinge stiffness properties.…”
Section: Introductionsupporting
confidence: 65%
“…and ̂ is a unit vector in the direction of the folding hinge axis, which is ̂= { cos −sin 0 } (18) The local angle of attack of the wingtip is related to the velocity vector through tan = 3 1 = sin cos − cos sin sin cos cos + sin sin sin + cos cos 2 (1 − cos ) (19) which yields = arctan ( tan cos − sin sin 1 + tan sin sin + sin 2 (cos − 1) )…”
Section: Acknowledgmentsmentioning
confidence: 99%